Hi All,
I'm loving learning Haskell quite a bit. It is stretching my brain but in a delightfull way. I've googled, I've hoogled but I haven't found a clear explanation for what exactly liftM2 does in the context below. Using the cool lambdabot "pointless" utility I found out that: > \x -> snd(x) - fst(x) is the same as: > liftM2 (-) snd fst I like the elegance of this but I cannot reconcile it with its type. I can't understand it. I check the signature of liftM2 and I get: Prelude> :t liftM2 Prelude> liftM2 :: (Monad m) => (a1 -> a2 -> r) -> m a1 -> m a2 -> m r Can someone help me understand what's happening here ? What does a Monad have to do with a simple subtraction ? What is actually the "m" of my example ? I am sure if I get this I'll be another step closer to illumination ... Thanks, Nick _______________________________________________ Haskell-Cafe mailing list [hidden email] http://www.haskell.org/mailman/listinfo/haskell-cafe |
Hi Nicola,
Am Montag, den 11.12.2006, 17:15 +0100 schrieb Nicola Paolucci: > Using the cool lambdabot "pointless" utility I found out that: > > > \x -> snd(x) - fst(x) > > is the same as: > > > liftM2 (-) snd fst > > I like the elegance of this but I cannot reconcile it with its type. I > can't understand it. > I check the signature of liftM2 and I get: > > Prelude> :t liftM2 > Prelude> liftM2 :: (Monad m) => (a1 -> a2 -> r) -> m a1 -> m a2 -> m r > > Can someone help me understand what's happening here ? > What does a Monad have to do with a simple subtraction ? > What is actually the "m" of my example ? You came across a very nice Monad: “((->) a)”, or the Monad of all functions that take a parameter of type a. Do not be confused by the arrow _before_ the a, it is actually behind the a: A function of type “a -> b” has type “(->) a b”. The same syntax as for infix operators applies, and can be curried to “((->) a)”. So in your example, snd and fst are computations in the ((->) (a,b)) Monad, and liftM2 (-) get’s the type: Num a => ((->) (a,a) a) -> ((->) (a,a) a) -> ((->) (a,a) a) or Num a => ((a,a) -> a) -> ((a,a) -> a) -> ((a,a) -> a) (at least I think so...) So if you ever feel like squaring something: square = join (*) Greetings, Joachim > > I am sure if I get this I'll be another step closer to illumination ... > > Thanks, > Nick > _______________________________________________ > Haskell-Cafe mailing list > [hidden email] > http://www.haskell.org/mailman/listinfo/haskell-cafe -- Joachim "nomeata" Breitner mail: [hidden email] | ICQ# 74513189 | GPG-Key: 4743206C JID: [hidden email] | http://www.joachim-breitner.de/ Debian Developer: [hidden email] _______________________________________________ Haskell-Cafe mailing list [hidden email] http://www.haskell.org/mailman/listinfo/haskell-cafe |
In reply to this post by Nicola Paolucci
Quoth Nicola Paolucci, nevermore:
> Prelude> :t liftM2 > Prelude> liftM2 :: (Monad m) => (a1 -> a2 -> r) -> m a1 -> m a2 -> m r > > Can someone help me understand what's happening here ? > What does a Monad have to do with a simple subtraction ? > What is actually the "m" of my example ? I'm honestly not sure what the actual Monad m is in this case. I'm sure some enlightened individual will help us out. Maybe Identity? But I thought you might find this handy --- the interactive console will give you the type of whole expressions, not just bare functions. It can be pretty helpful when trying to decode typery. > :t liftM2 > liftM2 :: (Monad m) => (a1 -> a2 -> r) -> m a1 -> m a2 -> m r > :t liftM2 (-) > liftM2 (-) :: (Num a1, Monad m) => m a1 -> m a1 -> m a1 > :t liftM2 (-) snd > liftM2 (-) snd :: (Num b) => ((a, b) -> b) -> (a, b) -> b > :t liftM2 (-) snd fst > liftM2 (-) snd fst :: (Num a) => (a, a) -> a Cheers, D. _______________________________________________ Haskell-Cafe mailing list [hidden email] http://www.haskell.org/mailman/listinfo/haskell-cafe |
In reply to this post by Nicola Paolucci
On 11/12/06, Nicola Paolucci <[hidden email]> wrote:
> Hi All, > > I'm loving learning Haskell quite a bit. > It is stretching my brain but in a delightfull way. > > I've googled, I've hoogled but I haven't found a clear explanation for > what exactly liftM2 does in the context below. > > Using the cool lambdabot "pointless" utility I found out that: > > > \x -> snd(x) - fst(x) > > is the same as: > > > liftM2 (-) snd fst > > I like the elegance of this but I cannot reconcile it with its type. I > can't understand it. > I check the signature of liftM2 and I get: > > Prelude> :t liftM2 > Prelude> liftM2 :: (Monad m) => (a1 -> a2 -> r) -> m a1 -> m a2 -> m r > > Can someone help me understand what's happening here ? > What does a Monad have to do with a simple subtraction ? > What is actually the "m" of my example ? > > I am sure if I get this I'll be another step closer to illumination ... > > Thanks, > Nick Hi Nick! The monad instance which is being used here is the instance for ((->) e) -- that is, functions from a fixed type e form a monad. So in this case: liftM2 :: (a1 -> a2 -> r) -> (e -> a1) -> (e -> a2) -> (e -> r) I bet you can guess what this does just by contemplating the type. (If it's not automatic, then it's good exercise) Now, why does it do that? Well, in general, liftM2 f x y = do u <- x v <- y return (f u v) So, it runs each of the computations you give it to get parameters for f, and then returns the result of applying f to them. In the ((->) e) monad, (which is often called the reader monad, because it's isomorphic to it), running a computation just means passing it the environment of type e. So in the reader monad, the environment is passed to each of x and y, to get u and v respectively, and then the value of (f u v) is returned. To translate, this is like: liftM2 f x y e = f (x e) (y e) of course, just for this particular monad. Another nice example is join. In general, join :: (Monad m) => m (m a) -> m a join x = do y <- x z <- y return z or simply, join x = do y <- x y In the reader monad, join has type (e -> e -> a) -> (e -> a), and it's somewhat obvious what it must be doing -- it must take the value of type e that it gets, and use it for both of the parameters of the function it gets in order to produce a value of type a. You can see by interpreting the do-notation that this is what happens in a curried way. First x is passed the environment, then its result (the partially applied function) is passed that environment. So, for instance, join (*) 5 will result in 25. The reader monad and functor instances are interesting, and worth exploring. There are some rather interesting idioms which can be obtained in this way. A nice one is: ap (,) f being the function (\x -> (x, f x)), which is handy for mapping across lists of x-coordinates in making plots of functions. Let us know if you need more detail about anything here. I sort of skipped over some details in the presentation. (You might want to work out exactly what return and bind do in this monad in order to understand things completely -- you can work them out from the types alone.) - Cale _______________________________________________ Haskell-Cafe mailing list [hidden email] http://www.haskell.org/mailman/listinfo/haskell-cafe |
In reply to this post by Nicola Paolucci
"Nicola Paolucci" <[hidden email]> writes:
> Hi All, > > I'm loving learning Haskell quite a bit. > It is stretching my brain but in a delightfull way. > > I've googled, I've hoogled but I haven't found a clear explanation for > what exactly liftM2 does in the context below. > > Using the cool lambdabot "pointless" utility I found out that: > > > \x -> snd(x) - fst(x) > > is the same as: > > > liftM2 (-) snd fst > > I like the elegance of this but I cannot reconcile it with its type. I > can't understand it. > I check the signature of liftM2 and I get: > > Prelude> :t liftM2 > Prelude> liftM2 :: (Monad m) => (a1 -> a2 -> r) -> m a1 -> m a2 -> m r > > Can someone help me understand what's happening here ? > What does a Monad have to do with a simple subtraction ? > What is actually the "m" of my example ? > > I am sure if I get this I'll be another step closer to illumination ... Does typing :t liftM2 (-) snd into ghc enlighten you at all? -- Jón Fairbairn [hidden email] _______________________________________________ Haskell-Cafe mailing list [hidden email] http://www.haskell.org/mailman/listinfo/haskell-cafe |
On 11 Dec 2006 16:55:17 +0000, Jón Fairbairn <[hidden email]> wrote:
> "Nicola Paolucci" <[hidden email]> writes: > > > Hi All, > > > > I'm loving learning Haskell quite a bit. > > It is stretching my brain but in a delightfull way. > > > > I've googled, I've hoogled but I haven't found a clear explanation for > > what exactly liftM2 does in the context below. > > > > Using the cool lambdabot "pointless" utility I found out that: > > > > > \x -> snd(x) - fst(x) > > > > is the same as: > > > > > liftM2 (-) snd fst > > > > I like the elegance of this but I cannot reconcile it with its type. I > > can't understand it. > > I check the signature of liftM2 and I get: > > > > Prelude> :t liftM2 > > Prelude> liftM2 :: (Monad m) => (a1 -> a2 -> r) -> m a1 -> m a2 -> m r > > > > Can someone help me understand what's happening here ? > > What does a Monad have to do with a simple subtraction ? > > What is actually the "m" of my example ? > > > > I am sure if I get this I'll be another step closer to illumination ... > > Does typing > > :t liftM2 (-) snd > > into ghc enlighten you at all? > Make sure to :m + Control.Monad.Reader first, because this instance unfortunately isn't in the Prelude. _______________________________________________ Haskell-Cafe mailing list [hidden email] http://www.haskell.org/mailman/listinfo/haskell-cafe |
In reply to this post by Cale Gibbard
Hi Cale !
On 12/11/06, Cale Gibbard <[hidden email]> wrote: > The monad instance which is being used here is the instance for ((->) > e) -- that is, functions from a fixed type e form a monad. > > So in this case: > liftM2 :: (a1 -> a2 -> r) -> (e -> a1) -> (e -> a2) -> (e -> r) > I bet you can guess what this does just by contemplating the type. (If > it's not automatic, then it's good exercise) Now, why does it do that? > > Well, in general, > liftM2 f x y = do > u <- x > v <- y > return (f u v) > > So, it runs each of the computations you give it to get parameters for > f, and then returns the result of applying f to them. > [...] > Let us know if you need more detail about anything here. I sort of > skipped over some details in the presentation. (You might want to work > out exactly what return and bind do in this monad in order to > understand things completely -- you can work them out from the types > alone.) Your answer was very thorough and very clear. I am honestly overwhelmed :D. Mind bending and rewarding. Thank you very much. I will be going through all your examples again slowly and with a console on the side so that I am sure I grok as much as I can. Regards, Nick _______________________________________________ Haskell-Cafe mailing list [hidden email] http://www.haskell.org/mailman/listinfo/haskell-cafe |
In reply to this post by Nicola Paolucci
> I'm loving learning Haskell quite a bit.
> It is stretching my brain but in a delightfull way. Great! > Using the cool lambdabot "pointless" utility I found out that: > >> \x -> snd(x) - fst(x) > > is the same as: > >> liftM2 (-) snd fst Yes, the '(->) c' monad is very handy. One way to think about it is viewing 'f :: c -> a' as a set of 'a''s, indexed by the set of 'c''s. The monad operations are then easily understood as doing things 'pointwise': given some specific index (e.g. 'x'), you use this index to select the appropriate value of every relevant indexed object (e.g. 'snd' and 'fst'), and then apply the unlifted function (e.g. '(-)') to those. Another way to write the above function is 'uncurry (flip (-))', or 'uncurry subtract'. Regards, Arie _______________________________________________ Haskell-Cafe mailing list [hidden email] http://www.haskell.org/mailman/listinfo/haskell-cafe |
In reply to this post by Cale Gibbard
Hi All, Hi Cale,
Can you tell me if I understood things right ? Please see below ... On 12/11/06, Cale Gibbard <[hidden email]> wrote: > The monad instance which is being used here is the instance for ((->) > e) -- that is, functions from a fixed type e form a monad. > > So in this case: > liftM2 :: (a1 -> a2 -> r) -> (e -> a1) -> (e -> a2) -> (e -> r) > I bet you can guess what this does just by contemplating the type. (If > it's not automatic, then it's good exercise) Now, why does it do that? So the way I have to reason on the output I get from ghci is: Prelude> :t liftM2 liftM2 :: (Monad m) => (a1 -> a2 -> r) -> m a1 -> m a2 -> m r The m stands for ((->) e), that is like writing (e -> a1): a function which will take an argument of type e and will return an argument of type a1. And so the above line has a signature that reads something like: liftM2 will takes 3 arguments: - a function (-) that takes two arguments and returns one result of type r. - a function (fst) that takes one argument and returns one result. - a function (snd) that takes one argument and returns one result. - the result will be a certain function that will return the same type r of the (-) function. - Overall to this liftM2 I will actually pass two values of type a1 and a2 and will get a result of type r. >From the type signature - correct me if I am wrong - I cannot actually tell that liftM2 will apply (-) to the rest of the expression, I can only make a guess. I mean I know it now that you showed me: > liftM2 f x y = do > u <- x > v <- y > return (f u v) If this is correct and it all makes sense, my next question is: - How do I know - or how does the interpreter know - that the "m" of this example is an instance of type ((->) e) ? - Is it always like that for liftM2 ? Or is it like that only because I used the function (-) ? I am trying to understand this bit by bit I am sorry if this is either very basic and easy stuff, or if all I wrote is completely wrong and I did not understand anything. :D Feedback welcome. Thanks again, Regards, Nick _______________________________________________ Haskell-Cafe mailing list [hidden email] http://www.haskell.org/mailman/listinfo/haskell-cafe |
The interpreter infers that m = (e ->) because of the types of snd and fst.
When snd and fst are considered as monadic computations in the (e ->) monad, there types are: Prelude> :t fst fst :: (a, b) -> a Prelude> :t snd snd :: (a, b) -> b Note that: (a, b) -> a =~= m a where m x = (a,b) -> x So if we apply liftM2 to fst and snd, then the m of the result has to be the same as the m of the arguments; thus the m of the result is ((a, b) ->). Now the type of (-) is: Prelude> :t (-) (-) :: (Num a) => a -> a -> a Thus the interpreter knows that the a and b in the ((a, b) ->) monad are actually the same. Finally we have: Prelude Control.Monad.Reader> :t liftM2 (-) snd fst liftM2 (-) snd fst :: (Num a) => (a, a) -> a Note that: (a, a) -> a =~= m a where m x = (a,a) -> x So each argument to liftM2 contributes constraints to the components of liftM2's general type: Prelude> :t liftM2 liftM2 :: (Monad m) => (a1 -> a2 -> r) -> m a1 -> m a2 -> m r snd forces m to be ((x,a2) ->) fst forces m to be ((a1,y) ->) (-) forces a1 and a2 to be the same The conjunction of these contraints forces {a1:=a, a2:=a, m:=(a,a) ->}. HTH, Nick On 12/11/06, Nicola Paolucci <[hidden email]> wrote: > Hi All, Hi Cale, > > Can you tell me if I understood things right ? Please see below ... > > On 12/11/06, Cale Gibbard <[hidden email]> wrote: > > The monad instance which is being used here is the instance for ((->) > > e) -- that is, functions from a fixed type e form a monad. > > > > So in this case: > > liftM2 :: (a1 -> a2 -> r) -> (e -> a1) -> (e -> a2) -> (e -> r) > > > I bet you can guess what this does just by contemplating the type. (If > > it's not automatic, then it's good exercise) Now, why does it do that? > > So the way I have to reason on the output I get from ghci is: > > Prelude> :t liftM2 > liftM2 :: (Monad m) => (a1 -> a2 -> r) -> m a1 -> m a2 -> m r > > The m stands for ((->) e), that is like writing (e -> a1): a function > which will take an argument of type e and will return an argument of > type a1. > > And so the above line has a signature that reads something like: > liftM2 will takes 3 arguments: > - a function (-) that takes two arguments and returns one result of type r. > - a function (fst) that takes one argument and returns one result. > - a function (snd) that takes one argument and returns one result. > - the result will be a certain function that will return the same type > r of the (-) function. > - Overall to this liftM2 I will actually pass two values of type a1 > and a2 and will get a result of type r. > > >From the type signature - correct me if I am wrong - I cannot actually > tell that liftM2 will apply (-) to the rest of the expression, I can > only make a guess. I mean I know it now that you showed me: > > > liftM2 f x y = do > > u <- x > > v <- y > > return (f u v) > > If this is correct and it all makes sense, my next question is: > - How do I know - or how does the interpreter know - that the "m" of > this example is an instance of type ((->) e) ? > - Is it always like that for liftM2 ? Or is it like that only because > I used the function (-) ? > > I am trying to understand this bit by bit I am sorry if this is either > very basic and easy stuff, or if all I wrote is completely wrong and I > did not understand anything. :D Feedback welcome. > > Thanks again, > Regards, > Nick > _______________________________________________ > Haskell-Cafe mailing list > [hidden email] > http://www.haskell.org/mailman/listinfo/haskell-cafe > Haskell-Cafe mailing list [hidden email] http://www.haskell.org/mailman/listinfo/haskell-cafe |
In reply to this post by Nicola Paolucci
Hi,
> So the way I have to reason on the output I get from ghci is: > > Prelude> :t liftM2 > liftM2 :: (Monad m) => (a1 -> a2 -> r) -> m a1 -> m a2 -> m r > > The m stands for ((->) e), that is like writing (e -> a1): a function > which will take an argument of type e and will return an argument of > type a1. > > And so the above line has a signature that reads something like: > liftM2 will takes 3 arguments: > - a function (-) that takes two arguments and returns one result of > type r. > - a function (fst) that takes one argument and returns one result. > - a function (snd) that takes one argument and returns one result. > - the result will be a certain function that will return the same type > r of the (-) function. > - Overall to this liftM2 I will actually pass two values of type a1 > and a2 and will get a result of type r. > >> From the type signature - correct me if I am wrong - I cannot >> actually > tell that liftM2 will apply (-) to the rest of the expression, I can > only make a guess. I mean I know it now that you showed me: > >> liftM2 f x y = do >> u <- x >> v <- y >> return (f u v) > > If this is correct and it all makes sense, my next question is: > - How do I know - or how does the interpreter know - that the "m" of > this example is an instance of type ((->) e) ? > - Is it always like that for liftM2 ? Or is it like that only because > I used the function (-) ? > > I am trying to understand this bit by bit I am sorry if this is either > very basic and easy stuff, or if all I wrote is completely wrong and I > did not understand anything. :D Feedback welcome. You can derive this yourself by assigning types to all parts of the expression and working things out, i.e., doing the type inference yourself. For example, liftM2 :: T1 = T2 -> T3 -> T4 -> T5 because liftM2 consumes three arguments. Furthermore, ghci gives you the type of liftM2, you know the type of (-) and the types of snd and fst. Therefore, T2 = (a -> a -> a) (type of (-)) T3 = (b,c) -> c (type of snd) T4 = (d,e) -> d (type of fst) and, by the type of liftM2 :: (f -> g -> h) -> m f -> m g -> m h, we also have T2 = (f -> g -> h) T3 = m f T4 = m g T5 = m h The two type expressions for T2 imply that f = g = h = a (type-wise, that is). And m f = (b,c) -> c = ((->) (b,c)) c m g = (d,e) -> d = ((-> (d,e)) d, because f = g this reduces to ((->) (c,c)) c and thus : m h = (c,c) -> c, because f = g = h This implies that the monad m = ((->) (c,c)) and h = c = a = f = g Thus: liftM2 (-) snd fst :: ((->) (a,a)) a = (a,a) -> a If I made any errors, please tell me. -- Andy _______________________________________________ Haskell-Cafe mailing list [hidden email] http://www.haskell.org/mailman/listinfo/haskell-cafe |
In reply to this post by Nicola Paolucci
On Tuesday 12 December 2006 08:57, Nicola Paolucci wrote:
> - How do I know - or how does the interpreter know - that the "m" of > this example is an instance of type ((->) e) ? > - Is it always like that for liftM2 ? Or is it like that only because > I used the function (-) ? It's the snd that forces the interpreter to infer the ((->) e) monad. You can guess from the type of liftM2 that the (-) won't supply any more information/constraints about m because m is is only mentioned in the snd and fst parts. If you use different monadic values, instead of snd and fst, then the m will end up constrained to a different monad Try these commands in GHCi to see what happens if you use something in the Maybe monad: Prelude> :m + Control.Monad Prelude Control.Monad> :t liftM2 liftM2 :: (Monad m) => (a1 -> a2 -> r) -> m a1 -> m a2 -> m r Prelude Control.Monad> :t liftM2 (-) liftM2 (-) :: (Num a1, Monad m) => m a1 -> m a1 -> m a1 Prelude Control.Monad> :t liftM2 (-) (Just 5) liftM2 (-) (Just 5) :: (Num a1) => Maybe a1 -> Maybe a1 Prelude Control.Monad> :t liftM2 (-) (Just 5) Nothing liftM2 (-) (Just 5) Nothing :: (Num a1) => Maybe a1 Prelude Control.Monad> liftM2 (-) (Just 5) Nothing Nothing Daniel _______________________________________________ Haskell-Cafe mailing list [hidden email] http://www.haskell.org/mailman/listinfo/haskell-cafe |
In reply to this post by Nicola Paolucci
On 12/11/06, Nicola Paolucci <[hidden email]> wrote:
> I am trying to understand this bit by bit I am sorry if this is either > very basic and easy stuff, or if all I wrote is completely wrong and I > did not understand anything. :D Feedback welcome. Don't apologise - I, for one, am finding this discussion very informative, and am reading the responses with interest. Thanks for starting the thread! Paul. _______________________________________________ Haskell-Cafe mailing list [hidden email] http://www.haskell.org/mailman/listinfo/haskell-cafe |
In reply to this post by Nicolas Frisby
Hi Nicolas,
On 12/11/06, Nicolas Frisby <[hidden email]> wrote: > The interpreter infers that m = (e ->) because of the types of snd and fst. > > When snd and fst are considered as monadic computations in the (e ->) > monad, there types are: > > Prelude> :t fst > fst :: (a, b) -> a > Prelude> :t snd > snd :: (a, b) -> b > > Note that: (a, b) -> a =~= m a where m x = (a,b) -> x > > So if we apply liftM2 to fst and snd, then the m of the result has to > be the same as the m of the arguments; thus the m of the result is > ((a, b) ->). Now the type of (-) is: > > Prelude> :t (-) > (-) :: (Num a) => a -> a -> a > > Thus the interpreter knows that the a and b in the ((a, b) ->) monad > are actually the same. Finally we have: > > Prelude Control.Monad.Reader> :t liftM2 (-) snd fst > liftM2 (-) snd fst :: (Num a) => (a, a) -> a > > Note that: (a, a) -> a =~= m a where m x = (a,a) -> x > > So each argument to liftM2 contributes constraints to the components > of liftM2's general type: > > Prelude> :t liftM2 > liftM2 :: (Monad m) => (a1 -> a2 -> r) -> m a1 -> m a2 -> m r > > snd forces m to be ((x,a2) ->) > fst forces m to be ((a1,y) ->) > (-) forces a1 and a2 to be the same > > The conjunction of these contraints forces {a1:=a, a2:=a, m:=(a,a) ->}. Really clearly exposed. Thanks a lot, it all starts to make perfect sense. The main point I was missing I now realize was that m in my example context meant a monadic computation in the (e ->) monad. Regards, Nick _______________________________________________ Haskell-Cafe mailing list [hidden email] http://www.haskell.org/mailman/listinfo/haskell-cafe |
In reply to this post by Nicola Paolucci
> Using the cool lambdabot "pointless" utility I found out that:
> >> \x -> snd(x) - fst(x) > > is the same as: > >> liftM2 (-) snd fst > > I like the elegance of this but I cannot reconcile it with its type. I > can't understand it. > I check the signature of liftM2 and I get: > > Prelude> :t liftM2 > Prelude> liftM2 :: (Monad m) => (a1 -> a2 -> r) -> m a1 -> m a2 -> m r > > Can someone help me understand what's happening here ? > What does a Monad have to do with a simple subtraction ? > What is actually the "m" of my example ? I think the simplest way to understand liftM and liftM2 are in terms of their do-notation: liftM op act = do x <- act return (op x) that is: perform the action, bind the result to x, compute (op x) and return that in the monad. Similarly for liftM2: liftM2 op act1 act2 = do x <- act1 y <- act2 return (x `op` y) in your case: liftM2 (-) snd fst = do x <- snd y <- fst return (x - y) this is in the monad of functions that require an argument. Snd is a function that takes an argument (a pair) and returns a value (the 2nd member of the pair). Similarly fst is a fnction that takes an argument. The whole do-block represents a function that takes an argument (also a pair). As usual, do-blocks combine several actions (in this case functions of one arguments) into a new action. The description for this one is: the function that, when given an argument (say "a") computes the snd item of the pair (snd a) binds, computes the fst item of the pair (fst a) and subtracts the two values (snd a - fst a). > Nick Tim Newsham http://www.thenewsh.com/~newsham/ _______________________________________________ Haskell-Cafe mailing list [hidden email] http://www.haskell.org/mailman/listinfo/haskell-cafe |
Nice explanation. However, at http://stackoverflow.com/questions/4119730/cartesian-product it was pointed out that this
cartProd :: [a] -> [b] -> [(a, b)] cartProd = liftM2 (,) is equivalent to the cartesian product produced using a list comprehension: cartProd xs ys = [(x,y) | x <- xs, y <- ys] I do not see how your method of explanation can be used to explain this equivalence? Nevertheless, can you help me to understand how liftM2 (,) achieves the cartesian product? For example, Prelude Control.Monad.Reader> liftM2 (,) [1,2] [3,4,5] [(1,3),(1,4),(1,5),(2,3),(2,4),(2,5)] Thank you! |
A good first step would be understanding how the other entry works:
cartProd :: [a] -> [b] -> [(a,b)] cartProd xs ys = do x <- xs y <- ys return (x,y) It is about halfway between the two choices. John On Thu, Feb 9, 2012 at 9:37 AM, readams <[hidden email]> wrote: > Nice explanation. However, at > http://stackoverflow.com/questions/4119730/cartesian-product it was pointed > out that this > > cartProd :: [a] -> [b] -> [(a, b)] > cartProd = liftM2 (,) > > is equivalent to the cartesian product produced using a list comprehension: > > cartProd xs ys = [(x,y) | x <- xs, y <- ys] > > I do not see how your method of explanation can be used to explain this > equivalence? Nevertheless, can you help me to understand how liftM2 (,) > achieves the cartesian product? For example, > > Prelude Control.Monad.Reader> liftM2 (,) [1,2] [3,4,5] > [(1,3),(1,4),(1,5),(2,3),(2,4),(2,5)] > > Thank you! > > -- > View this message in context: http://haskell.1045720.n5.nabble.com/Cannot-understand-liftM2-tp3085649p5470185.html > Sent from the Haskell - Haskell-Cafe mailing list archive at Nabble.com. > > _______________________________________________ > Haskell-Cafe mailing list > [hidden email] > http://www.haskell.org/mailman/listinfo/haskell-cafe _______________________________________________ Haskell-Cafe mailing list [hidden email] http://www.haskell.org/mailman/listinfo/haskell-cafe |
To understand how liftM2 achieves the cartesian product, I think
one way is to find liftM2's implementation and (>>=) implementation as part of []'s instantiation of the Monad class. You can find the first in Control.Monad, and the second in the standard prelude. Lists are monads, and as John (almost) said, liftM2 f x y is equivalent to liftM2 f m1 m2 = do x1 <- m1 x2 <- m2 return (f x1 x2) Which is syntactic sugar (fancy Haskell) for liftM2 f m1 m2 = m1 >>= (\x1 -> m2 >>= (\x2 -> return (f x1 x2))) In the prelude, you can find instance Monad [] where m >>= k = foldr ((++) . k) [] m Fhe right-hand side of (>>=) here is roughly equivalent to concat (map k m). The last step, which I leave as an exercise to the reader (I always wanted to say that), is use the right hand side of the definition of (>>=) for lists in the right hand side of liftM2 when applied to (,) and two lists. You can see the type of the function (,) (yes, comma is a function!) by executing, in ghci: :type (,) Cheers, Ivan. On 9 February 2012 19:23, John Meacham <[hidden email]> wrote: > A good first step would be understanding how the other entry works: > > cartProd :: [a] -> [b] -> [(a,b)] > cartProd xs ys = do > x <- xs > y <- ys > return (x,y) > > It is about halfway between the two choices. > > John > > On Thu, Feb 9, 2012 at 9:37 AM, readams <[hidden email]> wrote: >> Nice explanation. However, at >> http://stackoverflow.com/questions/4119730/cartesian-product it was pointed >> out that this >> >> cartProd :: [a] -> [b] -> [(a, b)] >> cartProd = liftM2 (,) >> >> is equivalent to the cartesian product produced using a list comprehension: >> >> cartProd xs ys = [(x,y) | x <- xs, y <- ys] >> >> I do not see how your method of explanation can be used to explain this >> equivalence? Nevertheless, can you help me to understand how liftM2 (,) >> achieves the cartesian product? For example, >> >> Prelude Control.Monad.Reader> liftM2 (,) [1,2] [3,4,5] >> [(1,3),(1,4),(1,5),(2,3),(2,4),(2,5)] >> >> Thank you! >> >> -- >> View this message in context: http://haskell.1045720.n5.nabble.com/Cannot-understand-liftM2-tp3085649p5470185.html >> Sent from the Haskell - Haskell-Cafe mailing list archive at Nabble.com. >> >> _______________________________________________ >> Haskell-Cafe mailing list >> [hidden email] >> http://www.haskell.org/mailman/listinfo/haskell-cafe > > _______________________________________________ > Haskell-Cafe mailing list > [hidden email] > http://www.haskell.org/mailman/listinfo/haskell-cafe _______________________________________________ Haskell-Cafe mailing list [hidden email] http://www.haskell.org/mailman/listinfo/haskell-cafe |
Dear Ivan,
A great explanation you have provided! It is very clear. Thank you so much! (You Haskell folks are so willing to help.) Wish there was something I knew that would be useful to you. Thank you. Sincerely, Richard E. Adams Applications Developer Las Vegas Valley Water District Email: [hidden email] Tel. (702) 856-3627 -----Original Message----- From: Ivan Perez [mailto:[hidden email]] Sent: Friday, February 10, 2012 12:28 PM To: [hidden email] Cc: Richard Adams; [hidden email] Subject: Re: [Haskell-cafe] Cannot understand liftM2 To understand how liftM2 achieves the cartesian product, I think one way is to find liftM2's implementation and (>>=) implementation as part of []'s instantiation of the Monad class. You can find the first in Control.Monad, and the second in the standard prelude. Lists are monads, and as John (almost) said, liftM2 f x y is equivalent to liftM2 f m1 m2 = do x1 <- m1 x2 <- m2 return (f x1 x2) Which is syntactic sugar (fancy Haskell) for liftM2 f m1 m2 = m1 >>= (\x1 -> m2 >>= (\x2 -> return (f x1 x2))) In the prelude, you can find instance Monad [] where m >>= k = foldr ((++) . k) [] m Fhe right-hand side of (>>=) here is roughly equivalent to concat (map k m). The last step, which I leave as an exercise to the reader (I always wanted to say that), is use the right hand side of the definition of (>>=) for lists in the right hand side of liftM2 when applied to (,) and two lists. You can see the type of the function (,) (yes, comma is a function!) by executing, in ghci: :type (,) Cheers, Ivan. On 9 February 2012 19:23, John Meacham <[hidden email]> wrote: > A good first step would be understanding how the other entry works: > > cartProd :: [a] -> [b] -> [(a,b)] > cartProd xs ys = do > x <- xs > y <- ys > return (x,y) > > It is about halfway between the two choices. > > John > > On Thu, Feb 9, 2012 at 9:37 AM, readams <[hidden email]> wrote: >> Nice explanation. However, at >> http://stackoverflow.com/questions/4119730/cartesian-product it was >> pointed out that this >> >> cartProd :: [a] -> [b] -> [(a, b)] >> cartProd = liftM2 (,) >> >> is equivalent to the cartesian product produced using a list comprehension: >> >> cartProd xs ys = [(x,y) | x <- xs, y <- ys] >> >> I do not see how your method of explanation can be used to explain >> this equivalence? Nevertheless, can you help me to understand how >> liftM2 (,) achieves the cartesian product? For example, >> >> Prelude Control.Monad.Reader> liftM2 (,) [1,2] [3,4,5] >> [(1,3),(1,4),(1,5),(2,3),(2,4),(2,5)] >> >> Thank you! >> >> -- >> View this message in context: >> http://haskell.1045720.n5.nabble.com/Cannot-understand-liftM2-tp30856 >> 49p5470185.html Sent from the Haskell - Haskell-Cafe mailing list >> archive at Nabble.com. >> >> _______________________________________________ >> Haskell-Cafe mailing list >> [hidden email] >> http://www.haskell.org/mailman/listinfo/haskell-cafe > > _______________________________________________ > Haskell-Cafe mailing list > [hidden email] > http://www.haskell.org/mailman/listinfo/haskell-cafe Haskell-Cafe mailing list [hidden email] http://www.haskell.org/mailman/listinfo/haskell-cafe |
Free forum by Nabble | Edit this page |